1999
DOI: 10.1038/sj.onc.1202614
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle dependent subcellular distribution of Cdc25B subtypes

Abstract: The dual speci®city phosphatase and oncogene Cdc25B has been implicated in the G2/M cell cycle checkpoint, but the mode by which it is regulated remains poorly understood. Regional subcellular redistribution of proteins represents a unique potential regulatory mechanism. Thus, we examined in live cells the subcellular localization characteristics of Cdc25B 2 and Cdc25B 3 fused to green¯uorescent protein. Cdc25B 2 partitioned primarily in the cytoplasm during G1 and progressively migrated to the nucleus as cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…One possible explanation of the discrepancies between the expression patterns reported for CDC25B at various stages of the cell cycle 4,[10][11][12][13] is the existence of a family of splice variants. A least three CDC25B variants exist in humans, resulting from the presence or absence of domains A and B (14 and 41 residues respectively) that are located within the amino-terminal regulatory region.…”
Section: Introductionmentioning
confidence: 88%
“…One possible explanation of the discrepancies between the expression patterns reported for CDC25B at various stages of the cell cycle 4,[10][11][12][13] is the existence of a family of splice variants. A least three CDC25B variants exist in humans, resulting from the presence or absence of domains A and B (14 and 41 residues respectively) that are located within the amino-terminal regulatory region.…”
Section: Introductionmentioning
confidence: 88%
“…In human three splicing variants (CDC25B1, CDC25B2 and CDC25B3) have been identified (Baldin et al, 1997). Until now only differences in the subcellular localization of CDC25B2 and CDC25B3 have been found (Woo et al, 1999), however, these differences were not observed by Davezac et al (2000). As for CDC25C, the CDC25B phosphatase is able to associate with 14-3-3 proteins (Conklin et al, 1995;Mils et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…In addition to protein levels and phosphorylation status, the subcellular distribution of the Cdc25 family may be an important regulator of G 2 /M transition. Using CHO cells, Woo et al (39) observed that Cdc25B partitioned primarily in the cytoplasm during G 1 and progressively migrated to the nucleus as cells transitioned from the S to the G 2 /M phase. It is reported that 14-3-3 binding to the Ser 323 site of Cdc25B directly inhibits the activity of Cdc25B in HeLa cells, thereby blocking the access FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%